FAKTOR-FAKTOR YANG MEMPENGARUHI PERKEMBANGAN KOTA BANJARBARU - MUHAMMAD SURYANSYAH (PPJP Universitas Lambung Mangkurat, 2018)
M. suryansyah, (2018), “Factors Affecting Banjarbaru City Development” This thesis writing under the guidance of Dr. H. Ahmad Yunani, SE, M.SiThis research was undertaken to (1) the influence of the number of industries, the number of transport, the number of housing on the development of the city of Banjarbaru together. (2) which influences the most dominant influence the development of Banjarbaru City.The object of this research was conducted in Kota Banjarbaru using 10-year time series data using multiple linear regression analysis..The results of this study indicate that the number of industries, the number of transport, and the number of homes affect together on the development of Banjarbaru City by conducting f. The most dominant factor influencing the development of Banjarbaru City individually is the number of transport. This is evidenced by a t test that shows the probability of transport <0.05.Keywords: City development, industry, transportation, housing.